2010
DOI: 10.1091/mbc.e09-11-0926
|View full text |Cite
|
Sign up to set email alerts
|

Neuralized Promotes Basal to Apical Transcytosis of Delta in Epithelial Cells

Abstract: In this article, it is shown that a pool of Delta localizes at the basolateral membrane of sensory organ precursor cells of Drosophila and of polarized MDCK cells and that Delta is endocytosed in a Neuralized-dependent manner from this basolateral membrane to allow for relocalization to the apical domain where it can bind and activate Notch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 40 publications
2
67
0
4
Order By: Relevance
“…5A-CЈ). Although the Rab11 function during pI cell division has not been directly tested owing to its role in cytokinesis, several findings indicate that the Delta ligand transits the Rab11 endosome to reach the pI daughter cell interface to promote Notch signalling and the specification of the pIIa cell fate (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005;Jafar-Nejad et al, 2005). Accordingly, we observed that fluorescently labelled internalized 2663 RESEARCH ARTICLE Centrosome movement regulation Delta antibodies can be found localized around the anterior pI centrosome during cytokinesis (Fig.…”
Section: Crmp Controls the Duration Of Rab11 Accumulation Around The mentioning
confidence: 68%
See 2 more Smart Citations
“…5A-CЈ). Although the Rab11 function during pI cell division has not been directly tested owing to its role in cytokinesis, several findings indicate that the Delta ligand transits the Rab11 endosome to reach the pI daughter cell interface to promote Notch signalling and the specification of the pIIa cell fate (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005;Jafar-Nejad et al, 2005). Accordingly, we observed that fluorescently labelled internalized 2663 RESEARCH ARTICLE Centrosome movement regulation Delta antibodies can be found localized around the anterior pI centrosome during cytokinesis (Fig.…”
Section: Crmp Controls the Duration Of Rab11 Accumulation Around The mentioning
confidence: 68%
“…In parallel, Delta is activated in the anterior pI daughter by a Neur-dependent mechanism. Neur promotes Delta endocytosis in the anterior pI daughter cell (Benhra et al, 2010;Le Borgne and Schweisguth, 2003b). The Delta recycling to the apical pIIa/pIIb interface is then accomplished through the Rab11 positive endosomes (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the mechanosensory bristles) located along the cuticle of the adult Drosophila, and is critically dependent on Notch: during a program of three rounds of asymmetric cell division [177,178], each division generates one daughter cell that assumes the signal-sending role and uses DSLs to activate Notch in its sibling, which acts as a signal-receiving cell [179]. In the signal-sending cells of SOP, Delta localizes both at the apical and at the basolateral membrane, while Notch accumulates apically [180]. By using a pulse chase antibody uptake assay coupled to confocal microscopy sectioning, it was demonstrated that the basolateral pool of Delta is continuously endocytosed and delivered to the apical PM, where the interaction with Notch is most likely to occur [180].…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…By using a pulse chase antibody uptake assay coupled to confocal microscopy sectioning, it was demonstrated that the basolateral pool of Delta is continuously endocytosed and delivered to the apical PM, where the interaction with Notch is most likely to occur [180]. This observation was extended by the same Authors to highly-polarized mammalian cells: by using a compartmentalized antibody uptake assay, they showed that Dll1 is similarly internalized from the basolateral membrane of Madin-Darby canine kidney cells and then transcytosed to the apical plasma membrane where Notch1 accumulates [180]. In a second set of experiments on SOP the function of two primary regulators of actin dynamics was explored, i.e.…”
Section: Mechanistic Modelsmentioning
confidence: 99%